DEVELOPMENT OF E-BOOKLET THEME OF FOOD SECURITY BASED ON SCIENCE LITERACY FOR STUDENTS OF JUNIOR HIGH SCHOOL CLASS IX - Nova Amalia; Suroso Mukti Leksono; Vica Dian Aprelia Resti (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2022)
Scientific literacy is the answer to prepare students to face the challenges of the 21st century. The resulting e-booklet product with the theme of food security based on science literacy is an alternative solution to improve students scientific literacy skills. The food security e-booklet contains food sources, substances contained in food and food processing methods which are compiled based on the integration of aspects of scientific literacy and problem based learning models. The research method used is the 4D development model developed by S. Thiagarajan, et al. (1974). However, the research on the development of this e-booklet was modified according to needs, consisting of the define, design, and develop stages. The assessment was carried out using a validation questionnaire that was assessed by a team of experts with two science education lecturers and one science teacher. The results of this study obtained the average value of the feasibility of the e-booklet on the theme of food security based on scientific literacy as a whole with a percentage of 84% in the very feasible category. Therefore, this e-booklet with the theme of food security reflects students' scientific literacy as a whole and is suitable for use. Keywords: e-booklet, scientific literacy, food security, problem based learning models